2010
DOI: 10.1007/s00210-010-0542-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel finding of a low-molecular-weight compound, SMTP-7, having thrombolytic and anti-inflammatory effects in cerebral infarction of mice

Abstract: Tissue plasminogen activator (t-PA) has a short therapeutic time window for administration (3 h) and carries a risk of promoting intracerebral hemorrhage. The aim of the present study was to investigate a therapeutic time window and frequency of hemorrhagic region by treatment with Stachybotrys microspora triprenyl phenol-7 (SMTP-7). Thrombotic occlusion was induced by transfer of acetic acid-induced thrombus at the right common carotid artery into the brain of mice. Infarction area, neurological score, edema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
59
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 19 publications
3
59
1
Order By: Relevance
“…5 SMTPs, a family of triprenyl phenol metabolites produced by Stachybotrys microspora, enhance plasminogen activation by modulating plasminogen conformation. [5][6][7] SMTP-7, one of the most potent congeners, is effective in treating thrombotic stroke in animal models, [8][9][10][11] possibly involving a neuroprotective mechanism. [10][11][12] The SMTP molecule consists of a tricyclic g-lactam moiety, a geranylmethyl group, and an N-linked side chain.…”
Section: Introductionmentioning
confidence: 99%
“…5 SMTPs, a family of triprenyl phenol metabolites produced by Stachybotrys microspora, enhance plasminogen activation by modulating plasminogen conformation. [5][6][7] SMTP-7, one of the most potent congeners, is effective in treating thrombotic stroke in animal models, [8][9][10][11] possibly involving a neuroprotective mechanism. [10][11][12] The SMTP molecule consists of a tricyclic g-lactam moiety, a geranylmethyl group, and an N-linked side chain.…”
Section: Introductionmentioning
confidence: 99%
“…5-7 SMTP-7, one of the most potent congeners, is effective in treating thrombotic stroke. [8][9][10][11] The SMTP molecule consists of a tricyclic g-lactam moiety, a geranylmethyl group, and an N-linked side chain. Our previous studies identified 26 SMTP congeners, most of which differ in the side chain.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16] SMTP enhances both activation and fibrin binding of plasminogen by modulating plasminogen conformation, [12][13][14]17,18 and one of the SMTP congeners is effective in treating thrombotic stroke. 19,20 The SMTP molecule consists of a tricyclic g-lactam moiety, an isoprene side-chain and an N-linked side-chain. Our previous studies identified 15 SMTP congeners, including staplabin and the 'D-series' stereoisomers.…”
Section: Introductionmentioning
confidence: 99%